Determinants of maternal near miss at tertiary care hospital: a retrospective study - Kumari, Shweta; Prasad, Rashmi; Dalmia, Kanchan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: A woman who experienced a severe complication and she nearly died, but she survived the severe health condition during pregnancy, childbirth or postpartum is considered as maternal near miss. The investigation of near miss cases not only gives the superior information about disease burden but also the quality of care received by the mother. Methods: A hospital based retrospective study carried out on 120 pregnant women seeking treatment at the hospital were included in the study. Mothers who met the criteria for maternal near miss were identified by review of records. Results: In the present study, out of the 120 near miss cases studied, 60 (50.0%) cases belonged to the age group 18-24 years which forms about half of the population studied. 38 (31.66%) cases belonged to 25-29 years group, 15 (12.50%) cases in 30-34 years group and 7 (5.83%) cases in 35 years and above age group. Also, 104 (86.66%) cases from rural area whereas only 16 (13.33%) cases came from urban area. Conclusions: In this study, the most common causes of maternal near misses were haemorrhage (48.33%), hypertension (20%), severe anaemia (13.33%), sepsis (10%), cardiac dysfunction (3.33%), renal dysfunction (0.83%), respiratory dysfunction (0.83%) and liver dysfunction (0.83%).